Journal of Dental School - Ansari, Ghasem (Journal of Dental School, 2019)
jdentsch.com), which aimed to reach a wider range of audience. The second objective of this major move was to attract more international researchers to engage with their publishable materials allowing a diversity of the author’s range. A further move has been adopted to involve new editorial board members providing a boost to impact leading to the journal’s external to its international recognition. In this respect, the ulti- mate goal is to index this valuable scientific research base product in international indexing systems. Journal of Dental School, Shahid Beheshti University of Medical Sciences has a long history and bright background in which it had achieved high national recognition for many years. While JDS is a dentally focused subjected journal, it covers a wide range of research in the field of dental science. Despite growing number of publi- cation sources including journals, there is a rising trend towards publication of original works ready to be published. The launch of well-established JDS is believed to provide a much-needed source for young researchers and academics to have their publications to their potential worldwide readers. This will also allow the scientific dental community to become aware of the research lines and products from Iran and those contributing from the rest of the world. JDS has also been aimed to enhance the quality and sound- ness of the research publication in the region with several inclusive workshops on items, such as standard review points for medical journals, writing a scientific article, standard citations, and referencing, clinical application of research outcomes, preparation of systematic reviews, and more through the last 2 years. This program is constantly repeated for accessibility of those interested. An online version of the courses can be reached on demand. Editorial board members encourage potential authors to submit their valuable works online to JDS for speedy consideration. Authors are cordially strived to cite the materials published in this journal in their articles in order to boost their productivity. Reader’s Interest and Recent Issues Contents The most recent issues published consist of variety of topics including material science ranging from dental implants to surgical approaches for management of malignancy, dental sedation, and its prospect in dentistry, radiographic imaging and new updates, developments in endodontic therapy, as well as new findings in restorative and esthetic dentistry. As it is evident both clinical and laboratory research works are covered in JDS and also animal studies are strongly invited for publication in JDS. Since the scope of JDS journal includes a wide range of topics in the field of dental science it is believed that JDS has provided the ground for all the disciplines of dentistry allowing various readers with their specialty to have direct access to the work of those in other disciplines. Since the JDS is the official publication of Dental School at Shahid Beheshti University of Medical Sciences, it has a close collaboration with many high-ranked academics in medicine who had and will serve as reviewers, as well as contributing legs to the interdisci- plinary research works. A broadened spectrum of work is expected to be published in JDS widening the range of audiences among the medical and dental professions. Evidence-based materials published in JDS are thoroughly reviewed in very restricted blinded and standard manner in order to make sure the pub- lished materials are based on the International Committee of Medical Journal Editors (ICMJE) guidelines and requirements for manuscripts for bibliographic references developed by National Library of Medicine (NLM) first published in 1979.